(untitled) - DeLue, Steven M. (Boston, 1997)
Contents: Past I Classical, Christian, and Machiavellian approaches; Past II modern and contemporary approaches to Civil Society; Past III critiques of Civil Society
Keywords: Civil society,Xã hội dân sự; Political science,Khoa học chính trị